Multifactorial Hypercalcemia and Literature Review on Primary Hyperparathyroidism Associated with Lymphoma - Maletkovic, Jelena (Hindawi Publishing Corporation, 2014)
The most common cause of hypercalcemia in hospitalized patients is malignancy. Primary hyperparathyroidism most commonly causes hypercalcemia in the outpatient setting. These two account for over 90% of all cases of hypercalcemia. Hypercalcemia can be divided into PTH-mediated and PTH-independent variants. Primary hyperparathyroidism, familial hypocalciuric hypercalcemia, familial hyperparathyroidism, and secondary hyperparathyroidism are PTH mediated. The most common PTH-independent type of hypercalcemia is malignancy related. Several mechanisms lead to hypercalcemia in malignancy-direct osteolysis by metastatic disease or, more commonly, production of humoral factors by the primary tumor also known as humoral hypercalcemia of malignancy that accounts for about 80% of malignancy-related hypercalcemia. The majority of HHM is caused by tumor-produced parathyroid hormone-related protein and less frequently production of 1,25-dihydroxyvitamin D or parathyroid hormone by the tumor. We report the rare case of a patient with hypercalcemia and diagnosed primary hyperparathyroidism. The patient had persistent hypercalcemia after surgical removal of parathyroid adenoma with recorded significant decrease in PTH level. After continued investigation it was found that the patient also had elevated 1,25-dihydroxyvitamin D and further studies confirmed a large spleen mass that was later confirmed to be a lymphoma. This is a rare example of two concomitant causes of hypercalcemia requiring therapy.